Digital Platforms for Maternal Health and Socioeconomic Development in Toro, Nigeria: Bridging Policy, Communication and Governance - Nasiru, Idi Nasiru; Muazu, Habeeb (African Journal of Stability and Development (AJSD), 2025)
Nigeria grapples with one of the world’s highest maternal mortality rates, with 556 deaths per 100,000 live births. This disproportionately affects rural communities such as Toro, Bauchi State, where access to healthcare is hindered by infrastructural deficits and patriarchal norms. While digital platforms such as mobile health (mHealth) applications, SMS reminders, and telemedicine offer transformative potential, their adoption remains hindered by digital literacy (57% of respondents), male gatekeepers (42%), and misalignment with governance frameworks. Grounded in Amartya Sen’s Capability Approach, this mixed-methods study evaluates how digital health tools can be leveraged to enhance maternal healthcare access while fostering socioeconomic development in Toro local government area of Bauchi State. By repositioning maternal health as a developmental imperative, this research advances strategies to achieve SDG 3 (Health) and SDG 5 (Gender Equity) while strengthening community resilience and governance frameworks in rural Nigeria. The research was carried out through a survey with 400 mothers and caregivers and six gender-segregated focus group discussions (FGDs) to capture socio-cultural nuances. Findings reveal that 68% of respondents reported improved antenatal care access through telemedicine and SMS reminders. Additionally, 34% leveraged mobile tools for income generation, which indirectly supported healthcare expenditures. Thematic analysis identified community-led training sessions and male advocacy campaigns as critical for bridging literacy gaps and challenging restrictive norms. For instance, women who participated in peer-led workshops were 3 times more likely to adopt digital health tools, illustrating the role of social modelling in shifting patriarchal dynamics. The study argues for integrating digital health into Nigeria’s National Development Plan (2021–2025) and National Digital Economy Policy (2020–2030) to institutionalise maternal care as a governance priority. Recommendations include decentralising healthcare funding to empower local leaders in co-designing voice-based apps in Hausa language and subsidising health-focused data plans through telecom partnerships. The study further emphasises aligning digital health interventions with Nigeria's National Development Plan (2021-2025) and the African Union's Agenda 2063 to foster sustainable development and gender equity.